Research advances of metal fluoride for energy conversion and storage - Runlin Zhang; Zijin Xu; Zeyu Hao; Zeshuo Meng; Xiufeng Hao; Hongwei Tian (Carbon Energy)
Abstract In recent years, renewable energy sources, which aim to replace rapidly depleting fossil fuels, face challenges due to limited energy storage and conversion technologies. To enhance energy storage and conversion efficiency, extensive research has been conducted in the academic community on numerous potential materials. Among these materials, metal fluorides have attracted significant attention due to their ionic metal–fluorine bonds and tunable electronic structures, attributed to the highest electronegativity of fluorine in their chemical composition. This makes them promising candidates for future electrochemical applications in various fields. However, metal fluorides encounter various challenges in different application directions. Therefore, we comprehensively review the applications of metal fluorides in the field of energy storage and conversion, aiming to deepen our understanding of their exhibited characteristics in different electrochemical processes. In this paper, we summarize the difficulties and improvement methods encountered in different types of battery applications and several typical electrode optimization strategies in the field of supercapacitors. In the field of water electrolysis, we focus on surface reconstruction and the critical role of fluorine, demonstrating the catalytic performance of metal fluorides from the perspectives of reconstruction mechanism and process analysis. Finally, we provide a summary and outlook for this field, aiming to offer guidance for future breakthroughs in the energy storage and conversion applications of metal fluorides.